2012
DOI: 10.1080/07448481.2011.599353
|View full text |Cite
|
Sign up to set email alerts
|

Collegiate-Based Emergency Medical Service: Impact on Alcohol-Related Emergency Department Transports at a Small Liberal Arts College

Abstract: CBEMS could promote a culture conducive to increased reporting behavior, which makes the campus safer. Similar BAC levels suggest that the degree of intoxication was similar for the 2 reporting periods, but students sought emergency assistance more frequently following the inception of CBEMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Many drug use and overdose cases begin with a 911 call that leads to a public safety or an ambulance response by the Emergency Medical Services (EMS) system. 9 Few studies have evaluated the association between activation of the ambulance system and alcohol and drug-related emergencies. Previous research has used EMS data to carry out public health surveillance of health conditions in the community at large, but this data has yet to include substance use of adolescents and young adults in a suburban community in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many drug use and overdose cases begin with a 911 call that leads to a public safety or an ambulance response by the Emergency Medical Services (EMS) system. 9 Few studies have evaluated the association between activation of the ambulance system and alcohol and drug-related emergencies. Previous research has used EMS data to carry out public health surveillance of health conditions in the community at large, but this data has yet to include substance use of adolescents and young adults in a suburban community in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have analyzed ambulance calls for alcohol-related emergencies 8 . Young people account for many alcohol-related calls, especially on college campuses 9 . Few studies have evaluated the association between activation of the ambulance system and alcohol and drug-related emergencies.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile, roving student responders who were intimately familiar with the campus environment and patient population were capable of responding to non-ambulatory patients and of identifying individuals in-need. In fact, it has been suggested that students may be more willing to approach or to receive care from peers, especially in cases of alcohol and other drugs 22 . Moreover, student responders were capable of informally obtaining pre-event information from peers regarding expected activities and illicit consumption patterns, which facilitated targeted pre-event training.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been suggested that students may be more willing to approach or to receive care from peers, especially in cases of alcohol and other drugs. 22 Moreover, student responders were capable of informally obtaining pre-event information from peers regarding expected activities and illicit consumption patterns, which facilitated targeted pre-event training. Similarly, student leaders of Skidmore College EMS were able to engage with event organizers, college administrators, and peer health educators to recommend safety precautions and contribute to prevention/awareness campaigns.…”
Section: Collegiate-based First Response Modelmentioning
confidence: 99%
“…Carey et al 14 found that alcohol intoxication was responsible for approximately 1 out of every 6 campus-based ambulance runs at a private fouryear residential university in the northeastern United States in [2005][2006]. Additionally, Rosen et al 15 reported that more than twice the number of students were transported to an emergency department for alcohol intoxication following the introduction of a CBEMS agency at a small liberal arts college in the northeastern United States in 2009. Although the study was limited in scale, the authors noted that the presence of CBEMS may promote a culture on college campuses that is conducive to increased reporting and care-seeking behavior.…”
mentioning
confidence: 99%